Pelatihan, Wordwall, Guru SD, Ev PELATIHAN PEMANFAATAN APLIKASI WORDWALL UNTUK MEMBANTU MEMPERMUDAH DALAM PEMBUATAN SOAL QUIZ/UJIAN DI YAYASAN SEKOLAH GHAFA - ummi, Khairul Ummi; Handika, Dinda Putri (Publikasi Pengabdian Masyarakat, 2025)
This training on the utilization of the Wordwall application was conducted to enhance teachers’ abilities in creating digital and interactive quizzes or exams. The event took place on October 19, 2024, at Yayasan Sekolah Ghafa and was attended by 13 elementary school teachers. Wordwall is a web-based platform that allows educators to design a variety of question formats such as multiple-choice, matching pairs, and educational games, usable both online and offline. During the training, participants were guided to understand the main features of Wordwall, from account creation, template selection, question input, to quiz distribution to students. The training was carried out in a face-to-face setting using a hands-on approach, enabling participants to actively practice and create their own quizzes. The results showed that all participants successfully developed quiz questions independently using the templates provided by Wordwall. Teachers expressed high enthusiasm for the use of this technology, recognizing it as a tool that simplifies assessment processes and increases student engagement in learning. This activity marks an important first step toward digital transformation within Yayasan Sekolah Ghafa. It is hoped that similar training programs will continue to support teachers in mastering educational technologies that foster effective, enjoyable, and modern teaching and learning experiences